2013
DOI: 10.1016/j.ajpath.2013.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Activated PAR-2 Regulates Pancreatic Cancer Progression through ILK/HIF-α–Induced TGF-α Expression and MEK/VEGF-A–Mediated Angiogenesis

Abstract: Tissue factor initiates the process of thrombosis and activates cell signaling through protease-activated receptor-2 (PAR-2). The aim of this study was to investigate the pathological role of PAR-2 signaling in pancreatic cancer. We first demonstrated that activated PAR-2 up-regulated the protein expression of both hypoxia-inducible factor-1α (HIF-1α) and HIF-2α, resulting in enhanced transcription of transforming growth factor-α (TGF-α). Down-regulation of HIFs-α by siRNA or YC-1, an HIF inhibitor, resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
2
31
0
2
Order By: Relevance
“…In addition to the well-known role of PAR-2 in the primary proliferation of various cancer cells [2,3], including pancreatic cancer [4], the results presented highlighted convincingly the importance of stromal host receptors relative to local progression in the orthotopic pancreatic cancer model. The authors recorded an increase in the average volume of primary tumours in wild-type animals compared with PAR-2 −/− knockouts.…”
Section: Par-2 In Various Carcinogenesis Models: Not the Only Particisupporting
confidence: 60%
“…In addition to the well-known role of PAR-2 in the primary proliferation of various cancer cells [2,3], including pancreatic cancer [4], the results presented highlighted convincingly the importance of stromal host receptors relative to local progression in the orthotopic pancreatic cancer model. The authors recorded an increase in the average volume of primary tumours in wild-type animals compared with PAR-2 −/− knockouts.…”
Section: Par-2 In Various Carcinogenesis Models: Not the Only Particisupporting
confidence: 60%
“…3), a potent angiogenic factor, by these cells (Chang et al, 2013;Dutra-Oliveira et al, 2012;Liu and Mueller, 2006;Zhang et al, 2012). Furthermore, these studies reported that activation of PAR 2 by either trypsin or PAR 2 -activating peptides resulted in signalling via a number of pathways, including PI3K-dependent Akt pathways and ERK1/2 and p38 MAPK pathways.…”
Section: Par 2 Signalling and Tumour Angiogenesismentioning
confidence: 98%
“…These growth factors form homo-or heterodimers, stimulate cell surface receptors which activate the major signaling transduction pathways like the Ras-mitogen activated protein kinase pathway, and act as potent mitogens and chemoattractants for smooth muscle cells, fibroblasts and endothelial cells (72)(73)(74)(75). Responses to VEGF include inflammation, cellular proliferation, migration and resistance to apoptosis.…”
mentioning
confidence: 99%